Analysis of Income and Welfare of Anchovy Capture and Pond Fishermen in Kumu and Rap-Rap Villages within the Context of Blue Economy Sustainability - Cornelia Timpal; Morshe Everly Lumansik; Julita Inggrinne Nelwan; Jola Silvana Kalangi; Yopie A. T. Pangemanan; Sjerly Maria Lumi; Lenda Lumenta; Lalira, James (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the income and welfare of anchovy pond farmers in Desa Kumu and Rap-Rap, Minahasa, within the framework of blue economy sustainability.. A quantitative approach with an explanatory descriptive design was employed, combining structured interviews, a validated questionnaire, and direct field observations. Data were analyzed using descriptive statistics and multiple linear regression, with classical assumption tests (normality, multicollinearity, heteroscedasticity) conducted to ensure model validity. The results show that the average net daily income for pond farmers ranges from IDR 100,000 to IDR 135,000, which is sufficient for household needs but subject to fluctuations due to market prices and environmental conditions. The regression model (R² = 0.76, F = 18.24, p < 0.01) reveals that direct market access (β = 0.55, p = 0.000) and working capital (β = 0.42, p = 0.002) have a significant positive impact on income, while operational costs have a significant negative effect (β = -0.38, p = 0.005). In contrast, the use of environmentally friendly technology does not show a significant influence (p = 0.162), primarily due to limited adoption. Most farmers rely on personal savings for capital and sell their produce through local collectors at non-negotiable prices. Although 80% have heard of the blue economy, practical understanding and implementation remain low, hindered by high equipment costs and lack of training. The discussion highlights that economic empowerment, particularly through improved market access and financial support, is more critical for immediate welfare improvement than environmental technology adoption. The findings extend previous research by integrating socio-economic and sustainability factors into a single analytical model. Based on these results, it is recommended that local authorities facilitate the establishment of marketing cooperatives, provide microfinance programs, and deliver targeted training on eco-friendly aquaculture practices to enhance both income and environmental sustainability.